2008
DOI: 10.1021/nl073322a
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Control of Cell Rolling in Two Dimensions through Surface Patterning of Receptors

Abstract: We envisioned that label-free control of the transport of cells in two dimensions through receptorligand interactions would enable simple separation systems that are easy to implement, yet retain the specificity of receptor-ligand interactions. Here we demonstrate nanomechanical control of cell transport in two dimensions via transient receptor-ligand adhesive bonds by patterning of receptors that direct cell rolling through an edge effect. HL-60 cells rolling on P-selectin receptor patterns were deflected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 38 publications
(123 reference statements)
2
53
0
Order By: Relevance
“…Most affinity-based separation techniques are based on ''capture and release'' methods, while continuous flow sorting would be more desirable in terms of sorting efficiency and selectivity. Karnik et al [58] implemented a slanted affinity pattern, on which interacting cells are allowed to roll along the edges of the pattern, to separate cells continuously based on the surface affinity.…”
Section: Affinity-based Separationmentioning
confidence: 99%
“…Most affinity-based separation techniques are based on ''capture and release'' methods, while continuous flow sorting would be more desirable in terms of sorting efficiency and selectivity. Karnik et al [58] implemented a slanted affinity pattern, on which interacting cells are allowed to roll along the edges of the pattern, to separate cells continuously based on the surface affinity.…”
Section: Affinity-based Separationmentioning
confidence: 99%
“…Note that the residence time in the present device is 2 minuets, while it takes 2 hours for the cells to exit the tubing connected to the outlets. It is also noted that the cell speed is three orders of magnitude larger than that used in Karnik et al [7]. In order to demonstrate the feasibility of high-speed cell sorting with the present device, we employ the polystyrene beads and examine the effect of the flow velocity over 2 μm-deep grooves.…”
Section: Resultsmentioning
confidence: 96%
“…9) and human umbilical-vein endothelial cells (HUVEC) has been successfully accomplished. Karnik et al [13] also reported lateral cell motion along the edge of a Pselectin pattern. However, the cell velocity in the present device is three orders of magnitude larger than that used in the their study, indicating much higher throughput.…”
Section: Continuous-flow Lateral Cell Sorting Using Antibody-immomentioning
confidence: 94%